2020
DOI: 10.1002/jpen.1794
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Critical Illness Patients Fail to Respond to Current Evidence‐Based Intensive Care Nutrition Secondarily to Persistent Inflammation, Immunosuppression, and Catabolic Syndrome

Abstract: Background Sepsis‐induced multiple‐organ failure (MOF) has plagued surgical intensive care units (ICUs) for decades. Early nutrition (principally enteral) improves hospital outcomes of high‐risk ICU patients. The purpose of this study is to document how the growing epidemic of chronic critical illness (CCI) patients responds to adequate evidence‐based ICU nutrition. Methods This retrospective post hoc subgroup analysis of an ongoing sepsis database identified 56 CCI patients who received early, adequate nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Among hospitalized patients with COVID‐19, acquired malnutrition and sarcopenia can result from a protracted hospitalization, marred by immobility and prolonged mechanical ventilation 42 . The role and dose of exogenous protein on muscle anabolism in critically ill patients with COVID‐19 is unclear 43 . Patients with COVID‐19, pneumonia, and hypoxemic respiratory failure managed with awake prone positioning or extracorporeal membrane oxygenation are at increased risk for acquired malnutrition because these therapies can limit nutrient delivery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among hospitalized patients with COVID‐19, acquired malnutrition and sarcopenia can result from a protracted hospitalization, marred by immobility and prolonged mechanical ventilation 42 . The role and dose of exogenous protein on muscle anabolism in critically ill patients with COVID‐19 is unclear 43 . Patients with COVID‐19, pneumonia, and hypoxemic respiratory failure managed with awake prone positioning or extracorporeal membrane oxygenation are at increased risk for acquired malnutrition because these therapies can limit nutrient delivery.…”
Section: Introductionmentioning
confidence: 99%
“…42 The role and dose of exogenous protein on muscle anabolism in critically ill patients with COVID-19 is unclear. 43 Patients with COVID-19, pneumonia, and hypoxemic respiratory failure managed with awake prone positioning or extracorporeal membrane oxygenation are at increased risk for acquired malnutrition because these therapies can limit nutrient delivery. The value of early enteral nutrition (EN), ω-3 fatty acids, specialized proresolving mediators, and micronutrient supplementation on maintaining gut epithelial barrier and optimizing immune function has been demonstrated in non-COVID-19 patients but not clearly in COVID-19 patients with critical illness.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted with 56 adult patients with CCI, despite receiving nutrition support according to the adult guidelines, sepsis survivors progressed into a chronic malnourished state. The recommendation of nutrition support for patients with CCI and PICS is limited, even for the adult population ( 39 ) . Therefore, future studies should investigate anabolic nutrition strategies so that patients progress more quickly to the recovery phase and also provide evidence for the development of protocols to optimise nutrition therapies ( 1 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the persistent inflammation, immunosuppression, and catabolism syndrome (PICS) may arise in some [ 9 , 18 , 28 ]. Metabolically, PICS is characterized by a persistent catabolic state and hormonal disruption leading to anabolic resistance and inflammation-induced cachexia [ 53 ].…”
Section: Energy Expenditurementioning
confidence: 99%
“…Furthermore, studies imply that nutrition delivery largely fails to reach nutritional goals in the post-ICU hospitalization phase, although very few studies set goals according to regular IC measurements [ 11 ]. Recent retrospective data shows that PICS patients are prone to worse long-term outcomes and lower survival when fed with current evidence-based protocol nutrition [ 53 ]. It has been suggested that high levels of protein, amino acids, and anabolic adjuncts such as insulin, might aid in overcoming anabolic resistance in PICS.…”
Section: Ic-guided Nutritionmentioning
confidence: 99%